Application Culture Mandar to Child Discipline in Kindergarten Al-Hisabah West Sulawesi Province - Fitriana Fitriana; Baharina Baharina; Amrullah Amrullah (Indonesian Journal of Early Childhood Education Studies, 2023)
The research is to look at the phenomenon of Mandar culture in teachers implementing local wisdom learning in shaping discipline in children. Habituation based on local wisdom by reducing cultural values in children. The purpose of this study was to determine how the application of Mandar culture to child discipline. The type of research used is a qualitative approach, this is because researchers want to describe clearly and in detail the events or an incident about the application of Mandar Culture to child discipline and get in-depth data about the data that is the focus of the research. Data collection techniques are done through observation, documentation, and interviews. Based on the results of the study, it shows that the culture of siri' (shame), turu' (obey), and sirondo-rondoi (cooperation) is instilled in learning habits in children during initial activities, then the teacher conveys examples of sirondo-rondoi (cooperation) habits of local residents, teachers use folk legend stories, slip local language when discussing with children so that this is what encourages children to do good things seen in the ability of children to come to school on time and dress neatly, turu' (obey) means that children listen and carry out what is conveyed by parents and teachers.